Structural and Functional Analysis of the Cell Division Protein MinDNg: Implications of the C-terminus - Abedin, Asma (Université d'Ottawa / University of Ottawa, 2011)
Gram-negative bacteria such as Escherichia coli and Neisseria gonorrhea undergo symmetric cell division controlled in part by the Min system constituting of MinC, MinD and MinE. MinDNg is a peripheral membrane ATPase that functions by recruiting cell division inhibitor MinCNg to the membrane where it prevents septation. The available crystallographic data of archeal monomeric MinD is not ideal for a dimeric bacterial MinD homolog since there is only 30-40% sequence identity between the two organisms. In addition, the C-terminus of monomeric MinD is disordered in the crystal structures, which lead us to utilize a 13 amino acid truncated mutant of MinDNg (MinDNg-13aaCT) and test for the importance of the C-terminus of MinDNg. Our results indicate that MinDNg-13aaCT does not oligomerize even in the presence of ATP, in contrast to wild type MinDNg where we detect some formation of a dimeric form. The loss of dimerization that we observe with MinDNg-13aaCT could not be attributed to incorrect protein folding since it retained similar stability to the wild-type protein and behaved like a well folded globular protein. By measuring MinDNg reaction rates over a range of magnesium concentrations, we obtain a sigmoidal shaped curve for wild type MinDNg with a hill co-efficient of 10 in the absence of MinE and a hill co-efficient of 3 in the presence of MinE, suggesting that cooperativity is an inherent feature of MinDNg. In contrast, MinDNg-13aaCT has lost its ATPase activity rendering this mutant catalytically inactive. In addition our in vivo analysis illustrates that wildtype and MinDNg-13aaCT show a range of morphologies from long filamentous cells to minicells with this effect more pronounced in the case of wildtype MinDNg than compared to the mutant, which suggests that MinDNg-13aaCT has possibly retained its ability to interact with other Min proteins. In aggregate, our results provide some new insight into the structural and the functional role and importance of the C-terminus of MinDNg.